Correlation Between Resting Testosterone/Cortisol Ratio and Sound-Induced Vasoconstriction at Fingertip in Men - Ooishi, Yuuki (Frontiers in Physiology, 2018)
A sound-induced sympathetic tone has been used as an index for orienting responses to auditory stimuli. The resting testosterone/cortisol ratio is a biomarker of social aggression that drives an approaching behavior in response to environmental stimuli, and a higher testosterone level and a lower cortisol level can facilitate the sympathetic response to environmental stimuli. Therefore, it is possible that the testosterone/cortisol ratio is correlated with the sound-induced sympathetic tone. The current study investigated the relationship between the resting testosterone/cortisol ratio and vasoconstriction induced by listening to sound stimuli. Twenty healthy males aged 29.0 ± 0.53 years (mean ± S.E.M) participated in the study. They came to the laboratory for 3 days and listened to one of 3 types of sound stimuli for 1 min on each day. Saliva samples were collected for an analysis of salivary testosterone and cortisol levels on the day of each experiment. After the collecting the saliva sample, we measured the blood volume pulse (BVP) amplitude at a fingertip. Since vasoconstriction is mediated by the activation of the sympathetic nerves, the strength of the reduction in BVP amplitude at a fingertip was called the BVP response (finger BVPR). No difference was observed between the sound-induced finger BVPR for the 3 types of sound stimuli (p = 0.779). The correlation coefficient between the sound-induced finger BVPR and the salivary testosterone/cortisol ratio within participants was significantly different from no correlation (p = 0.011) and there was a trend towards a significance in the correlation between the sound-induced finger BVPR and the salivary testosterone/cortisol ratio between participants (r = 0.39, p = 0.088). These results suggest that the testosterone/cortisol ratio affects the difference in the sound-evoked sympathetic response.